Loss of the AKT2/3 potassium channel affects sugar loading into the phloem of Arabidopsis - Sauer, Norbert; et al. (Planta, 2002)
Members of the AKT2/3 family have been identified as photosynthate-induced phloem K channels. Here we describe the isolation and characterisation of an AKT2/3 loss-of-function mutant (akt2/3-1) from Arabidopsis thaliana (L.) Heynh. Microautoradiography following CO incubation in the light revealed that a major fraction of CO-derived photosynthates leaking out of sieve tubes appears not to be effectively reloaded (retrieval) into the phloem of the mutant. Using the aphid stylectomy technique we showed that the phloem sap of the mutant, lacking the phloem channels of the AKT2/3 type, contained only half the sucrose content of the wild type. Furthermore, the akt2/3-1 mutant exhibited a reduced K dependence of the phloem potential. Xenopus oocytes expressing the phloem sucrose/proton symporter depolarise upon sucrose application. When, however, the phloem channel was co-expressed - mimicking the situation in the sieve tube/companion cell complex - depolarisation was prevented. From our studies we thus conclude that AKT2/3 regulates the sucrose/H symporters via the phloem potential.
Keywords: Arabidopsis; Development (akt2/3-1 mutant); Phloem; Potassium channel; Sugar loading